Samsung Galaxy Tabs for dummies / Dan Gookin - Gookin, Dan
Blast into the Samsung Galaxy and experience your tablet in a whole new way. Gookin helps you get the most out of your Galaxy Note or Galaxy Tab and all its amazing features